2021
DOI: 10.1093/eurheartj/ehab029
|View full text |Cite
|
Sign up to set email alerts
|

Stress-associated neurobiological activity associates with the risk for and timing of subsequent Takotsubo syndrome

Abstract: Aims Activity in the amygdala, a brain centre involved in the perception of and response to stressors, associates with: (i) heightened sympathetic nervous system and inflammatory output and (ii) risk of cardiovascular disease. We hypothesized that the amygdalar activity (AmygA) ratio is heightened among individuals who develop Takotsubo syndrome (TTS), a heart failure syndrome often triggered by acute stress. We tested the hypotheses that (i) heightened AmygA precedes development of TTS and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 26 publications
3
48
0
Order By: Relevance
“…The amygdala activity using [18F] fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDGPET/CT) was measured retrospectively in 104 patients who underwent clinical 18F-FDG-PET/CT imaging, including 41 who subsequently developed TTS and 63 matched controls. Patients with subsequent TTS had higher baseline amygdala activity and, among the patients who developed TTS, those with higher amygdala activity developed TTS about 2 years earlier compared with those with lower level of amygdala activity (97).…”
Section: Brain-heart Axismentioning
confidence: 88%
See 1 more Smart Citation
“…The amygdala activity using [18F] fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDGPET/CT) was measured retrospectively in 104 patients who underwent clinical 18F-FDG-PET/CT imaging, including 41 who subsequently developed TTS and 63 matched controls. Patients with subsequent TTS had higher baseline amygdala activity and, among the patients who developed TTS, those with higher amygdala activity developed TTS about 2 years earlier compared with those with lower level of amygdala activity (97).…”
Section: Brain-heart Axismentioning
confidence: 88%
“…These neuroimaging findings demonstrate structural and functional alterations of stress-related brain networks in patients with TTS even before the acute event, suggesting long-lasting psychological stress. Chronically heightened stress-associated neural activity may hypothetically induce an individual to react to subsequent stressors with a more vigorous neurophysiological response, thus increasing TTS risk (97). Consequently "heartbrain axis" could represent a potential target to reduce TTS risk.…”
Section: Brain-heart Axismentioning
confidence: 99%
“… 11 Possibly, the mechanisms of effective combination therapy involve a reduction in sympathetic activity or the suppression of inflammatory reactions through interactions with the renin–angiotensin system. 12 However, a recent study demonstrated that combination therapy lacked efficacy for TTS recurrence. 1 Our case is worthwhile as the heterogeneous TTS recurrences occurred in the same individual.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-differences in brain activation patterns during emotional stimuli have been reported, particularly in the amygdala and ACC, with women demonstrating greater activation during negative emotion ( 56 ). In particular, heightened amygdalar activity appears to be related to increased risk of Takotsubo syndrome, a condition that is often triggered by emotional or physical stress and predominates in women ( 57 ).…”
Section: Sex/gender and Chest Pain And The Central Nervous Systemmentioning
confidence: 99%